Pertussis immunization during pregnancy: results of a cross-sectional study among Italian healthcare workers - Licata, Francesca; Romeo, Marika; Di Gennaro, Gianfranco; Citrino, Emma Antonia; Bianco, Aida (Frontiers in Public Health, 2023)
Background This study aimed to assess whether Italian healthcare workers (HCWs) recommend the reduced antigen content tetanus-diphtheria-acellular pertussis vaccination (Tdap) to pregnant people, as well as what variables could predict their decision to advise and recommend immunization to pregnant people. Methods This cross-sectional study took place between August 2021 and June 2022 in a sample of obstetricians-gynecologists, midwives, and primary-care physicians in two regions of Southern Italy. A self-administered questionnaire was used to gather the data. Results The results showed 91.3% (379) of participants knew that receiving the Tdap vaccine during pregnancy protects against pertussis in both the expectant person and the newborn before active immunization. Only 68.9% (286) knew that the Tdap vaccination has to be administered during the third trimester of gestation. A small but still significant proportion of participants (14.7%) (61) believed that the potential risks of vaccines administered during pregnancy outweighed the benefits. An improvable proportion of HCWs regularly provided information [71.8% (298)] and recommended [81% (336)] Tdap vaccination to pregnant people. The strongest factors that drove HCWs to inform pregnant people about the Tdap vaccination were to be aware that vaccinating those in close contact with newborns is an effective strategy to prevent pertussis (OR: 2.38; 95% CI: 1.11–5.13) and that the Tdap vaccine is provided only in the third trimester of pregnancy (OR: 1.74; 95% CI: 1.06–2.86). Informing pregnant people about the possibility of receiving the Tdap vaccine during pregnancy (OR: 60.13; 95% CI: 23.50–153.8) was the strongest predictor of having recommended the Tdap vaccination during pregnancy. Conclusion Educational and informative interventions to improve HCWs’ knowledge about the importance of the Tdap vaccine and their communication skills to properly counsel pregnant people are needed. Beyond vaccine recommendations, how well immunization strategies are implemented in real-world situations impacts vaccination uptake. Therefore, during regular care visits, expecting people must have easy access to vaccines. Prenatal immunizations should become common practice, and there should be no conceptual doubt about vaccinations among HCWs to safeguard pregnant people and their unborn children from vaccine-preventable diseases.